(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
In this article, the inhibition efficiency of the corrosion inhibitor obtained on the basis of monoethanolamine, methyl methacrylate and phosphoric acid was studied by electrochemical methods, Electrochemical impedance spectroscopy (EIS) measurements and potentiodynamic polarization measurements